Model Pengelolaan Dana Desa untuk Mencapai Suistainable Development Goals di Desa Suci, Kecamatan Panti, Kabupaten Jember - Oryza Ardhiarisca; Rahma Rina Wijayanti; Dessy Putri Andini; Avisenna Harkat; Adelia Eka Puspita Ansori; Muhammad Hanip; Siti Anisa (Politeknik Ganesha Medan, 2026)
SDGs is an international sustainable development program that was later adapted into the Village. SDGs in Indonesia with a context that has been adapted to villages in Indonesia. SDGs are ideals that villages, including Suci Village, aspire to realize. This is because the national development goal is to achieve the four pillars of the SDGs: social development, economic development, and legal development and governance. These four pillars are the oldest of the 17 aspects of the SDGs. This study aims to determine and map the village fund management model implemented by the Suci Village Government in realizing sustainable village development according to the four pillars of the SDGs. This research is a qualitative descriptive study. Data collection was conducted through interviews, documentation, and observation. The research informants were the village head, the head of financial affairs, and the village operator. Secondary data in this study were obtained from the RPJMDes, APBDes LRA, Village Profile. Data validity was tested by triangulating sources and methods. The results of the study indicate that village fund management in Suci Village is quite good. The programs planned in Suci Village are in line with the SDGs objectives. Likewise, the implementation of these activities has been very good. This is evidenced by the increase in the APBDes portion to support the SDGs which increased in 2024 from Rp381,642,500.00 to Rp735,934,000.00 in 2025. The implications of this study are expected to improve integration of Waste Bank-BUMDes, and pre-feasibility of PLTMH. The limitations of this study have not yet tested the outcomes of the programs planned and implemented by the Suci Village government